2017
DOI: 10.1074/jbc.m117.805937
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-302a suppresses influenza A virus–stimulated interferon regulatory factor-5 expression and cytokine storm induction

Abstract: During influenza A virus (IAV) infection, cytokine storms play a vital and critical role in clinical outcomes. We have previously reported that microRNA (miR)-302c regulates IAV-induced IFN expression by targeting the 3'-UTR of nuclear factor κB (NF-κB)-inducing kinase. In the current study, we found that miR-302a, another member of the miR-302 cluster, controls the IAV-induced cytokine storm. According to results from cell-based and knockout mouse models, IAV induces a cytokine storm via interferon regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…Nevertheless, the overall effect of OGT in the IAV-induced cytokine storm remains unknown. We recently reported that IAV induces cytokine storm via interferon (IFN) regulatory factor-5 (IRF5) (19). In this study, we found that genetic deletion of OGT markedly impaired IAV-induced cytokine storm in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Nevertheless, the overall effect of OGT in the IAV-induced cytokine storm remains unknown. We recently reported that IAV induces cytokine storm via interferon (IFN) regulatory factor-5 (IRF5) (19). In this study, we found that genetic deletion of OGT markedly impaired IAV-induced cytokine storm in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 81%
“…IRF5, a member of the IRF family, is critical for regulating immune and inflammatory responses in health and disease (19). IRF5 contains a DNA binding domain, an IRF-association domain, and a serinerich region (SRR) at the C terminus (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNAs have been shown to play key roles in the regulation of IAV-induced inflammatory response by controlling the pro-inflammatory intracellular signaling pathways. miR-302a is known to inhibit IAV replication by controlling interferon regulatory factor-5 (IRF-5) expression and cytokine storm induction [46]. Upregulation of miR-4776 in Influenza Virus infected primary human bronchial epithelial cells suppress IκB β, which further promotes cell survival [47].…”
Section: Discussionmentioning
confidence: 99%